Negative electrode active material and method for manufacturing the same, negative electrode sheet, battery, and electrical device
Patent Information
- Application Number
- JP2025528954
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-03-13
- Filing Date
- 2023-11-03
- Publication Date
- 2026-10-22
- Estimated Expiration
- 2043-11-03
AI Technical Summary
【0005】 本出願の負極活物質は、従来技術に対して少なくとも次の有益な効果を有する。1、該負極活物質により、炭素材料の高導電率、安定性及びシリコン材料の高容量化を両立し、負極シートに用いると負極の容量及び導電性の向上、電池のエネルギー密度及び電気的性能の改善に有利である。2、シリコン系粒子は炭素コア及び多孔質炭素骨格層に分布しており、即ち、シリコン系粒子は最外層の炭素被覆層の内側に分布していることにより、多孔質炭素骨格層の多孔質構造及び最外層の炭素被覆層によって、充放電サイクル中のシリコンの体積膨張を効果的に抑制し、負極活物質の構造安定性を向上させることができることによって、サイクル中に発生し得る負極シート及び電池の体積膨張を効果的に改善し、電池のサイクル性能を向上させることができる。3、製造プロセスが制御可能であり、炭素コア及び多孔質炭素骨格層の存在する領域におけるシリコン系粒子の配向分布を波吸収材料により実現することができる。
Smart Images

Figure 0007940114000003 
Figure 0007940114000004 
Figure 0007940114000005
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of batteries, and specifically, relates to a negative electrode active material, a method for producing the same, a negative electrode sheet, a battery, and an electric device. BACKGROUND ART
[0002] Lithium-ion batteries feature eco-friendliness, high energy, and low carbon properties, and are widely applied not only in energy storage power supply systems such as hydropower, thermal power, wind power and photovoltaic power plants, but also in various fields including electric transportation means such as electric bicycles, electric motorcycles and electric vehicles, as well as military equipment and aerospace. With the development of current society, the requirements for lithium-ion batteries are also increasing, for example, high energy density is being demanded. The negative electrode is an important component of a lithium-ion battery, and a high-capacity negative electrode active material contributes to the improvement of the energy density of the battery. For example, a silicon-based negative electrode active material can improve the energy density of the battery. SUMMARY OF THE INVENTION
[0003] In view of the technical problems existing in the background art, the present application provides a negative electrode active material aiming at improving the energy density and cycle performance of a battery.
[0004] To achieve the above object, in a first aspect of the present application, there is provided a negative electrode active material, comprising: a carbon core; a porous carbon skeleton layer having an accommodating space inside, wherein the carbon core is located in the accommodating space; a carbon coating layer covering at least a part of the outer surface of the porous carbon skeleton layer; and wave-absorbing materials and silicon-based particles that are each independently distributed in the regions where the carbon core and the porous carbon skeleton layer are present, respectively.
[0005] The negative electrode active material of this application has at least the following beneficial effects compared to the prior art: 1. The negative electrode active material achieves both high conductivity and stability of the carbon material and high capacity of the silicon material, and when used in a negative electrode sheet, it is advantageous for improving the capacity and conductivity of the negative electrode, and improving the energy density and electrical performance of the battery. 2. The silicon-based particles are distributed in the carbon core and the porous carbon skeleton layer, that is, the silicon-based particles are distributed inside the outermost carbon coating layer. The porous structure of the porous carbon skeleton layer and the outermost carbon coating layer effectively suppress the volume expansion of silicon during the charge-discharge cycle, improving the structural stability of the negative electrode active material. This effectively improves the volume expansion of the negative electrode sheet and battery that may occur during the cycle, and improves the battery's cycle performance. 3. The manufacturing process is controllable, and the orientation distribution of silicon-based particles in the region where the carbon core and porous carbon skeleton layer exist can be realized using a wave-absorbing material.
[0006] In some embodiments of this application, the content of the wave-absorbing material distributed in the porous carbon skeleton layer is 90 wt% or more based on the total mass of the wave-absorbing material, and the content of the wave-absorbing material distributed in the region where the carbon core is present is 10 wt% or less. By having the distribution amount of the wave-absorbing material within a predetermined range, more silicon can be deposited in the deeper parts of the pores of the porous carbon skeleton layer, and the volume expansion of silicon-based particles can be effectively suppressed by the porous structure of the porous carbon skeleton and the carbon coating layer, thereby improving cycle performance.
[0007] In some embodiments of this application, the content of the wave-absorbing material is 0.5 wt% to 15 wt% by mass of the porous carbon framework layer. By controlling the amount of wave-absorbing material added within a predetermined range, silicon can be deposited more readily in the region where the porous carbon framework layer and carbon core exist, without excessively occupying the internal space of the negative electrode active material, thereby achieving a high silicon deposition rate. ,negative This is advantageous for achieving both high volume per gram and high dynamic performance of the most active material.
[0008] In some embodiments of this application, the content of the wave-absorbing material is 10 wt% or less by mass of the negative electrode active material, and selectively 3 wt% to 8 wt%. By controlling the amount of wave-absorbing material added within a predetermined range, silicon can be deposited more readily in the region where the porous carbon skeleton layer and carbon core exist, without excessively occupying the internal space of the negative electrode active material, thereby achieving a high silicon deposition rate. ,negative This is advantageous for achieving both high volume per gram and high dynamic performance of the most active material.
[0009] In some embodiments of this application, the wave-absorbing material satisfies at least one of the following conditions: a wave absorption range of 5.2 GHz to 15.9 GHz, a wave absorption bandwidth of 8.4 GHz to 10.7 GHz, and a particle size of 20 nm to 500 nm. Controlling the particle size of the wave-absorbing material within a predetermined range is further advantageous in improving the uniformity of the distribution of the wave-absorbing material and silicon-based particles within the anode active material, improving the amount of silicon deposited within the anode active material, and improving the capacity per gram and dynamic performance of the anode active material.
[0010] In some embodiments of this application, the wave-absorbing material comprises one or more of elemental metals, alloys, metal oxides, composite metal oxides, carbides, and sulfides, and selectively comprises one or more of elemental iron, iron-containing alloys, and iron-containing oxides. Selecting a wave-absorbing material within a predetermined range is advantageous for achieving precise heating at specific locations and for uniformly oriented deposition of more silicon inside the negative electrode active material, particularly in the pores of the multilayer carbon skeleton layer.
[0011] In some embodiments of this application, the silicon-based particles include one or more of silicon elemental, silicon oxygen material, and silicon carbon material. Silicon-based particles within a predetermined range have a high capacity, which can increase the total capacity per gram of the negative electrode active material.
[0012] In some embodiments of this application, the content of silicon-based particles is 30 wt% to 70 wt% by mass of the negative electrode active material, and selectively 30 wt% to 50 wt%. By controlling the content of silicon-based particles within a predetermined range, it is possible to achieve both high volume per gram and high cycle stability of the negative electrode active material.
[0013] In some embodiments of this application, the porosity of the porous carbon framework layer is 40% to 70%. By controlling the porosity of the porous carbon framework layer within a predetermined range, it is possible to improve the volume per gram and cycle stability of the anode active material while ensuring the overall strength of the anode active material.
[0014] In some embodiments of this application, the pore size of the porous carbon skeleton layer is 1 nm to 50 nm. Controlling the pore size of the porous carbon skeleton layer within a predetermined range may be further advantageous in improving the capacity per gram of the negative electrode active material and the stability of the cycle structure.
[0015] In some embodiments of this application, the negative electrode active material satisfies at least one of the following conditions: the particle size of the carbon core is 1 μm to 5 μm; the thickness of the carbon coating layer is 1 μm or less, selectively 0.2 μm or less, more selectively 0.1 μm or less, and even more selectively 0.05 μm to 0.08 μm; and the Dv50 particle size of the negative electrode active material is 10 μm or less, and the Dv90 particle size is 20 μm or less.
[0016] In some embodiments of this application, the carbon core comprises one or more of graphite, porous carbon, and mesocarbon microbeads, wherein the porous carbon optionally comprises hard carbon.
[0017] In some embodiments of this application, the carbon precursor material used to form the porous carbon skeleton layer and the carbon coating layer each independently comprises one or more of pitch, resin, soluble starch, sucrose, glucose, and polyacrylic acid ester.
[0018] In some embodiments of this application, the negative electrode active material further includes a carbon core coating layer that covers at least a portion of the outer surface of the carbon core, is located in the containment space, and has a wave-absorbing material distributed within it. By satisfying the above conditions, the deposition of silicon throughout the interior of the negative electrode active material can be further promoted, the silicon content on the surface of the negative electrode active material can be reduced, and the inhibitory effect of the negative electrode active material on the volume expansion of silicon-based particles during charge-discharge cycles can be improved.
[0019] In some embodiments of this application, the mass ratio of the wave-absorbing material to the carbon core coating layer is greater than the mass ratio to the porous carbon skeleton layer. Satisfying this condition may further be advantageous in that more silicon is deposited inside the porous carbon skeleton layer, and the amount of silicon deposited on the side of the porous carbon skeleton layer closer to the carbon core is greater than the amount of silicon deposited on the side closer to the carbon coating layer.
[0020] In some embodiments of this application, the thickness of the carbon core coating layer is 1 μm or less, selectively 0.3 μm to 1 μm, and more selectively 0.3 μm to 0.5 μm. By controlling the thickness of the carbon core coating layer within a predetermined range, it is possible to promote the deposition of more silicon throughout the interior of the anode active material, improve cycle performance, and further secure the total volume per gram of the anode active material.
[0021] In some embodiments of this application, the negative electrode active material has a resistivity of 100 mΩ·cm to 10,000 mΩ·cm at room temperature and a pressure of 4 MPa, and selectively, 100 mΩ·cm to 300 mΩ·cm. By controlling the resistivity of the negative electrode active material to a predetermined range, its volume effect and cycle performance can be improved, and dynamic performance can be ensured.
[0022] In a second aspect of the present application, provided is the method for producing the negative electrode active material according to the first aspect of the present application, comprising the steps of: mixing a carbon core material, a pore-forming agent, a carbon skeleton precursor material, and a solvent to obtain a first mixed solution; mixing a wave-absorbing material with the first mixed solution to obtain a second mixed solution; subjecting the second mixed solution to spray forming and fluidized drying treatment to obtain composite particles; subjecting the composite particles to carbonization treatment and activation treatment to obtain skeleton particles in which the carbon core is coated with a porous carbon skeleton layer; performing microwave heating on the skeleton particles, and introducing a gas-phase silicon source to deposit silicon, so as to obtain precursor particles; and coating at least a part of the outer surface of the precursor particles with a carbon coating layer, so as to obtain the negative electrode active material.
[0023] Compared with the prior art, the method for producing the negative electrode active material according to the present application at least has the following beneficial effects: the production process is controllable, heating can be performed with high precision through the wave-absorbing material and microwave heating, the oriented distribution of silicon is realized, and the negative electrode active material with a desired structure can be obtained; in addition, it is beneficial to lowering the heating temperature and heating time during production, improving the production efficiency and reducing the cost, and the produced negative electrode active material can effectively suppress the volume expansion of silicon and improve its structural stability during cycles.
[0024] In some embodiments of the present application, before preparing the first mixed solution, the method further comprises a step of coating at least a part of the outer surface of the carbon core material with a carbon core coating layer.
[0025] In some embodiments of the present application, the pore-forming agent includes one or more of sodium chloride, potassium chloride, zinc chloride, sodium carbonate, potassium carbonate, zinc carbonate, zinc acetate, and ammonium acetate.
[0026] In some embodiments of the present application, the sum of the mass proportion of the pore-forming agent and the mass proportion of the carbon skeleton precursor material in the first mixed solution is 10 wt% to 70 wt%.
[0027] In some embodiments of the present application, the mass ratio of the pore-forming agent to the carbon skeleton precursor material is (10 to 1):(1 to 100), optionally (10 to 1):(2 to 10), and further optionally (10 to 1):(2 to 5). Controlling the usage amount of the pore-forming agent within a predetermined range may be further advantageous for obtaining a porous carbon skeleton layer with a desired porosity and a micro-mesoporous porous structure.
[0028] In a third aspect of the present application, a negative electrode sheet is provided, which comprises the negative electrode active material according to the first aspect of the present application and / or the negative electrode active material produced by the method for producing a negative electrode active material according to the second aspect of the present application.
[0029] In a fourth aspect of the present application, a battery is provided, which comprises the negative electrode active material according to the first aspect of the present application, and / or the negative electrode active material produced by the method for producing a negative electrode active material according to the second aspect of the present application, and / or the negative electrode sheet according to the third aspect of the present application.
[0030] In a fifth aspect of the present application, an electrical apparatus is provided, which comprises the negative electrode active material according to the first aspect of the present application, and / or the negative electrode active material produced by the method for producing a negative electrode active material according to the second aspect of the present application, and / or the negative electrode sheet according to the third aspect of the present application, and / or the battery according to the fourth aspect of the present application.
[0031] Additional aspects and advantages of the present application will be set forth in part in the description that follows, and in part will become apparent from the description or may be learned by practice of the present application. Brief Description of the Drawings
[0032] The above and / or additional aspects and advantages of the present application will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings. [Figure 1] It is a schematic cross-sectional structural view of a negative electrode active material according to an embodiment of the present application. [Figure 2] It is a schematic cross-sectional structural view of a negative electrode active material according to another embodiment of the present application. [Figure 3] It is a schematic structural view of a battery according to an embodiment of the present application. [Figure 4] This is a schematic diagram of the structure of a battery module according to one embodiment of this application. [Figure 5] This is a schematic diagram of the structure of a battery pack according to one embodiment of this application. [Figure 6] This is an exploded view of a battery pack according to one embodiment of the present application. [Figure 7] This is a schematic diagram of one embodiment of an electrical device powered by a battery according to one embodiment of the present application. [Figure 8] This is the XRD spectrum of the negative electrode active material produced according to Example 1 of this application. [Figure 9] This is the XRD spectrum of the negative electrode active material produced by Comparative Example 1 of this application. [Modes for carrying out the invention]
[0033] The present application will be further described below with reference to specific embodiments. It should be understood that these specific embodiments are for illustrative purposes only and do not limit the scope of the present application.
[0034] In this application, “Examples” means that certain features, structures, or characteristics described in association with an example may be included in at least one example of this application. The term “Examples” appearing elsewhere in the specification does not necessarily refer to the same example, nor does it mean that an example is exclusively independent or alternative to another example. It will be explicitly or implicitly understood by those skilled in the art that the examples described in this application may be combined with other examples.
[0035] The “range” disclosed in this application is limited in the form of a lower limit and / or upper limit, and a given range is limited by selecting one lower limit and / or one upper limit, and the selected lower limit and / or upper limit defines the boundary of a special range. The thus limited range may or may not include endpoint values and can be combined in any way, that is, any lower limit and any upper limit can be combined to form an unspecified range, and any lower limit and any lower limit can be combined to form an unspecified range, and similarly, any upper limit and any upper limit can be combined to form an unspecified range. In addition, each individually disclosed point or individual numerical value can itself, as a lower limit or upper limit, be combined with any other point or individual numerical value, or with other lower limits or upper limits, to form an unspecified range. For example, if a range of 20 or less is listed for a particular parameter, it is understood that ranges satisfying 20 or less, such as 2 to 18 and 5 to 15, are also expected. Furthermore, if 1 and 5 are listed as the minimum range values and 10 and 30 are listed as the maximum range values, then the ranges 1-10, 1-30, 5-10, and 5-30 are all conceivable. In this application, unless otherwise specified, the numerical range "30-100" represents an abbreviated expression of any combination of real numbers between 30 and 100, where both 30 and 100 are real numbers. For example, the numerical range "1-30" means that all real numbers between "1-30" have already been listed herein, and "1-30" is merely an abbreviated expression of combinations of these numbers.
[0036] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions, and such technical solutions should be considered to be included in the disclosures of this application.
[0037] Unless otherwise specified, all technical features and optional technical features of this application can be combined to form new technical solutions, and such technical solutions should be considered to be included in the disclosures of this application.
[0038] Unless otherwise specified, all steps of this application may be performed sequentially or randomly, preferably in order. For example, if the method includes steps S1 and S2, it means that the method may include steps S1 and S2 performed sequentially, or steps S2 and S1 performed sequentially. For example, if it is stated that the method may further include step S3, it means that step S3 may be added to the method in any order, for example, the method may include steps S1, S2 and S3, or steps S1, S3 and S2, or steps S3, S1 and S2.
[0039] Unless otherwise specified, descriptions such as "includes" and "inclusive" in this application may be open or closed. For example, such descriptions as "includes" and "inclusive" may further include or include other components not listed, or may include or include only the listed components. Also, in this application, the terms "multiple" and "multiple types" refer to two or more.
[0040] Unless otherwise specified, the term "and / or" in this application simply describes the relationship between related objects, indicating that three relationships may exist. For example, A and / or B can represent three cases: when A exists alone, when A and B exist simultaneously, and when B exists alone. In addition, the symbol " / " in this specification generally indicates that the preceding and following related objects are in an "or" relationship.
[0041] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those generally understood by those skilled in the art to which this application pertains. The terms used in this application are solely for the purpose of describing specific embodiments and are not intended to limit this application. Terms such as “includes,” “has,” and any variations thereof in the description, claims, and brief description of the drawings above are intended to cover the non-exclusive “includes.” Unless otherwise stated, the terms used in this application have the well-known meanings generally understood by those skilled in the art. Unless otherwise stated, the numerical values of each parameter mentioned in this application can be measured by various measurement methods commonly used in the art (for example, by the methods shown in the embodiments of this application).
[0042] Currently, as the demand for power batteries gradually increases, the demand for higher energy density in power batteries is also growing. However, silicon-based materials with high energy density experience significant volume expansion during the cycle process, and this can reach up to 300% when silicon nanoparticles are deeply embedded in lithium batteries. Normally, the expansion effect of silicon can be effectively suppressed by compounding carbon materials of different structures and dimensions, but a large amount of silicon may be free outside the carbon structure. For example, there is a process in which a silicon dispersion is added drop by drop to a vigorously stirred metal oxide-graphene dispersion, a metal oxide-graphene-silicon composite material is obtained by suction filtration, and then a porous graphene-silicon anode material is obtained by acid etching and carbon thermal reaction. However, this process is not only costly in terms of raw materials, but it is also difficult to deposit silicon inside the active material. Such silicon distributed on the surface directly increases the electron conduction resistance between particles, and the expansion due to silicon exposed on the surface of the material during the cycle also affects the cycle life.
[0043] In view of this, a first aspect of the present application provides a negative electrode active material. As shown in Figure 1, the negative electrode active material includes a carbon core 10, a porous carbon skeleton layer 20, a carbon coating layer 30, a wave-absorbing material (not shown), and silicon-based particles (not shown), wherein the interior of the porous carbon skeleton layer 20 has a housing space (not shown) capable of accommodating the carbon core 10, and the carbon core 10 is located in this housing space. The carbon coating layer 30 covers at least a portion of the outer surface of the porous carbon skeleton layer 20. The wave-absorbing material and silicon-based particles are each independently distributed within the regions where the carbon core 10 and the porous carbon skeleton layer 20 are present, and for example, both may be independently distributed, in part or all, in the voids of the skeleton of the porous carbon skeleton layer 20.
[0044] According to the embodiments of this application, by combining a carbon material and silicon-based particles to form the above structure, the negative electrode active material achieves both the high conductivity and stability of the carbon material and the high capacity of the silicon material. When used in a negative electrode sheet, it is advantageous for improving the capacity and conductivity of the negative electrode, and for improving the energy density and electrical performance of the battery. On the other hand, in the negative electrode active material, the silicon-based particles are distributed in the carbon core and the porous carbon skeleton layer, that is, the silicon-based particles are distributed inside the outermost carbon coating layer. The porous structure of the porous carbon skeleton layer and the outermost carbon coating layer effectively suppress the volume expansion of silicon during charge-discharge cycles, improving the structural stability of the negative electrode active material. This effectively improves the volume expansion of the negative electrode sheet and battery that may occur during cycles, thereby improving the battery's cycle performance. Furthermore, the manufacturing process of the negative electrode active material is controllable, and the orientation distribution of silicon-based particles in the region where the carbon core and porous carbon skeleton layer exist can be realized using a wave-absorbing material.
[0045] Furthermore, the negative electrode active material described in the first aspect of this application satisfies the above conditions, and its performance, including but not limited to capacity, conductivity, and cycle stability, can be further improved by controlling the distribution position, amount, and wave absorption range of the wave-absorbing material, as well as the selection and amount of silicon-based particles, the structure of the porous carbon skeleton layer, and the selection of carbon cores. That is, in addition to satisfying the above conditions, one or more of the following conditions may be selectively satisfied.
[0046] In some embodiments of this application, the content of the wave-absorbing material distributed in the porous carbon skeleton layer 20 is greater than the content of the wave-absorbing material distributed in the region where the carbon core 10 is located. In silicon-carbon composite negative electrode active materials, a large amount of silicon is free outside the carbon structure or exposed on the surface of the material because conventional heat treatment methods for silicon-carbon composite materials require high temperatures, long sintering temperatures, and consume a large amount of energy, and it is not possible to accurately control the temperature of different regions of the material. In such conventional heat treatment process modes, it is difficult to control the finished state of the silicon-carbon composite material, and a large amount of energy is consumed. Furthermore, because the silicon does not easily penetrate into the carbon skeleton, many silicon crystal particles exist on the surface of the material, which easily causes serious expansion problems during battery cycling, directly affects the structural stability of the silicon-carbon composite material, and ultimately affects the cycle performance. In contrast to the adverse effects of conventional heat treatment on silicon-carbon composite materials, introducing a wave-absorbing material into the silicon-carbon composite material allows for the coupling of the wavelength range of the wave-absorbing material with the basic microstructure of the material to generate heat, enabling precise heating of specific locations within the material. This also offers advantages such as a rapid heating rate, high energy utilization rate, high heating efficiency, safety, hygiene, and no contamination. In the embodiments of this application, by distributing a larger amount of wave-absorbing material in the porous carbon framework layer, a heating method that heats the entire material uniformly without gradients due to its own heat generation during the manufacturing of the negative electrode active material, and a rapid heating rate, allows for the deposition of more silicon in the depths of the pores of the porous carbon framework layer. This means that silicon penetrates into the interior of the negative electrode active material, significantly reducing its content on the surface of the negative electrode active material. Furthermore, it effectively suppresses the volume expansion of silicon, which is advantageous for maintaining the structural stability of silicon-based particles during long-term cycles. Additionally, the carbon coating layer further suppresses the volume expansion of internal silicon-based particles, improving cycle performance.
[0047] In some embodiments of this application, the content of wave-absorbing material distributed in the porous carbon skeleton layer 20 on a basis of the total mass of the wave-absorbing material may be 90 wt% or more (for example, 91 wt%, 92 wt%, 93 wt%, 94 wt%, 95 wt%, 96 wt%, 97 wt%, 98 wt%, 99 wt%, etc., or within a range of any of the above values), and the content of wave-absorbing material distributed in the region where the carbon core 10 exists may be 10 wt% or less (for example, 9 wt%, 8 wt%, 7 wt%, 6 wt%, 5 wt%, 4 wt%, 3 wt%, 2 wt%, 1 wt%, etc., or within a range of any of the above values). The presence or absence of wave-absorbing material can be determined by the intensity signal of the negative electrode active material in an electromagnetic wave environment. For example, in the case of silicon-containing negative electrode active material, the presence or absence of wave-absorbing material may be determined after etching the silicon, or the crystal type or type of wave-absorbing material may be determined by XRD testing, or the type and content of component elements in minute regions within the cross-sectional area of the negative electrode active material may be analyzed using an energy-dispersive X-ray analyzer (EDS) to determine the distribution of wave-absorbing material in different regions and to analyze the mass ratio of wave-absorbing material in different regions. In the embodiments of this application, by ensuring that the distribution of wave-absorbing material satisfies the above predetermined conditions, more silicon can be deposited in the depths of the pores of the porous carbon skeleton layer, and the volume expansion of silicon-based particles can be effectively suppressed by combining the porous structure of the porous carbon skeleton with the carbon coating layer, thereby improving cycle performance.
[0048] In some embodiments of this application, the content of the wave-absorbing material may be 0.5 wt% to 15 wt% based on the mass of the porous carbon framework layer 20, for example, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, etc., or it may be within any range of the above values. The content of the wave-absorbing material in the porous carbon framework layer can be obtained by analyzing the types and content of component elements in the porous carbon framework layer region in the cross-section of the negative electrode active material using XRD testing and energy-dispersive X-ray analysis (EDS). Here, as the content of wave-absorbing material increases, the risk of aggregation into large particles within the porous carbon framework layer also increases, which tends to reduce the uniformity of the dispersion of the wave-absorbing material and significantly reduces the wave-absorbing effect. By coating the inside of the negative electrode active material structure with a small amount of wave-absorbing material, it is possible to precisely heat and control silicon deposition. By controlling the amount of wave-absorbing material added within a predetermined range, silicon can be deposited more easily in the region where the porous carbon framework layer and carbon core exist without excessively occupying the internal space of the negative electrode active material, thereby achieving a high silicon deposition amount. ,negative This is advantageous for achieving both high volume per gram and high dynamic performance of the most active material.
[0049] In some embodiments of this application, the content of the wave-absorbing material may be 10 wt% or less by mass of the negative electrode active material, for example, 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, etc., or within any range of the above values. By controlling the amount of wave-absorbing material added within a predetermined range, it becomes easier to deposit more silicon in the region where the porous carbon skeleton layer and carbon core exist without excessively occupying the internal space of the negative electrode active material, thereby achieving a high silicon deposition amount. ,negativeThis is advantageous in achieving both the capacity per gram and the dynamic performance of the anode active material. Selectively, the content of the wave-absorbing material may be 3 wt% to 8 wt% based on the mass of the anode active material. By controlling the amount of wave-absorbing material added within a predetermined range, it is possible to achieve a high silicon deposition rate while further avoiding the wave-absorbing material occupying extra internal space within the anode active material, thereby improving the capacity per gram and dynamic performance of the anode active material.
[0050] In some embodiments of this application, the wave absorption range of the wave-absorbing material may be 5.2 GHz to 15.9 GHz, for example, 6 GHz, 7 GHz, 8 GHz, 9 GHz, 10 GHz, 11 GHz, 12 GHz, 13 GHz, 14 GHz, 15 GHz, or any of the above values. The range of the absorption frequency range of the wave-absorbing material can be measured by placing the negative electrode active material (desiliconization treatment may be performed first if silicon is deposited) in an electromagnetic wave environment capable of specific frequency conversion and collecting the intensity signal of the electromagnetic wave. Selectively, the wave absorption range of the wave-absorbing material may be 6 GHz to 10 GHz. By selecting a wave absorption range within a predetermined range, it is advantageous to improve the heating efficiency and effect of the wave-absorbing material in a specific wavelength range, improve manufacturing efficiency, and reduce production costs.
[0051] In some embodiments of this application, the wave absorption bandwidth of the wave absorbing material may be 8.4 GHz to 10.7 GHz, for example, 8.5 GHz, 9 GHz, 9.5 GHz, 10 GHz, 10.5 GHz, or any of the above values within a given range. The wave absorption bandwidth is the frequency bandwidth, i.e., the difference in frequency between the maximum and minimum values of the absorption wavelength.
[0052] In some embodiments of this application, the particle size of the wave-absorbing material may be between 20 nm and 500 nm, for example, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 500 nm, or any of the above values within a given range. The particle size of the wave-absorbing material can be measured by a transmission electron microscope. For example, in the case of an Fe-based wave-absorbing material, the wave-absorbing material is in the form of solid particles, and its particle size can be observed with a high-magnification transmission electron microscope. The particles are dark in the field of view, and the average particle size of the particles in the field of view can be calculated. In the actual operation, multiple measurements may be taken and the average value obtained. Using wave-absorbing material with a small particle size is advantageous not only for increasing the number of wave-absorbing particles and improving the surface activity of the wave-absorbing material, but also for uniformly dispersing the wave-absorbing material. This promotes the conversion of electromagnetic energy to thermal energy under microwave field radiation, enabling precise heating at specific locations. Furthermore, it allows for the uniform orientation and deposition of more silicon within the anode active material, particularly in the pores of the multilayer carbon skeleton layer. This reduces the adverse effects of excessively large particle sizes on the uniform dispersion of the wave-absorbing material in the porous carbon skeleton layer, as well as the adverse effects on the uniform distribution of silicon-based particles and the amount deposited within the anode active material. Controlling the particle size of the wave-absorbing material within a predetermined range is further advantageous for improving the uniformity of the distribution of wave-absorbing material and silicon-based particles within the anode active material, improving the amount of silicon deposited within the anode active material, and improving the capacity per gram and dynamic performance of the anode active material.
[0053] In some embodiments of this application, the wave-absorbing material may include one or more of elemental metals, alloys, metal oxides, composite metal oxides, carbides, and sulfides, and may include, but is not limited to, silicon carbide, iron, copper, zinc, calcium, titanium, chromium and related derivatives (e.g., alloys, metal oxides such as FeO, Fe3O4, Fe2O3, ZnO, or composite metal oxides such as LaFeO3, LaSrFeO3), as well as oxides such as MoO2, NiO, TiO2, Co3O4, and WO3. Selectively, the wave-absorbing material may contain one or more of elemental iron, iron-containing alloys, and iron-containing oxides, for example, one or more of Fe, FeO, Fe3O4, and Fe2O3. The manufacturing process for the iron-containing wave-absorbing material within a predetermined range involves heating metal ions in situ to convert them into metal oxides, resulting in particles with small particle size (average particle size generally 100 nm or less, selectively 20 nm to 50 nm) dispersed within a porous carbon framework layer (partially nanoscale particles). Both the wave-absorbing material and the porous carbon material in the composite structure possess wave-absorbing properties, and electromagnetic synergy can improve impedance matching after the composite of the wave-absorbing material and carbon material, thereby enhancing electromagnetic wave absorption performance. At the same time, the iron-containing wave-absorbing material within the predetermined range has a small particle size and a relatively large number of surface atoms, which enhances the surface activity of the material and provides good magnetic permeability. Under microwave radiation, the motion of atoms and electrons becomes more vigorous, promoting magnetization and converting electrical energy into thermal energy. Conversely, this can improve the overall ability of the composite material to absorb, attenuate, and convert electromagnetic waves. This is further advantageous for achieving precise heating at specific locations and allows for the uniform orientation and deposition of more silicon inside the negative electrode active material, particularly in the pores of the multilayer carbon skeleton layer, thereby improving the capacity per gram and dynamic performance of the negative electrode active material.
[0054] In some embodiments of this application, the silicon-based particles include, but are not limited to, one or more of silicon elemental, silicon oxygen material, and silicon carbon material. Here, silicon-based particles within a predetermined range have high capacity, which can increase the capacity per gram of the entire negative electrode active material and improve the energy density of the battery.
[0055] In some embodiments of this application, the silicon-based particle content may be 30 wt% to 70 wt% by mass of the negative electrode active material, for example, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, or any of the above values within a range. The silicon-based particle content in the negative electrode active material can be obtained by ICP testing, specifically by measuring according to the EPA 6010D-2014 standard. For example, in ICP-OES (elemental analysis-inductively coupled plasma emission spectroscopy) testing, the solid to be measured is first dissolved in a liquid with a strong acid, then the liquid is introduced into an ICP light source by atomization, and the gaseous atoms to be measured are ionized and excited by a strong magnetic field, and then returned from the excited state to the ground state. Energy is released during the above process and recorded as different characteristic spectral lines, allowing for quantitative analysis of trace elements. Increasing the silicon-based particle content is advantageous for increasing the overall capacity per gram of the negative electrode active material. By keeping the silicon-based particle content within a reasonable range, it is possible to reduce the risk that excessive silicon-based particle content will cause the overall expansion of the negative electrode active material during charge-discharge cycles to exceed the adjustment limit of the core-shell composite structure of the negative electrode active material, thus affecting cycle performance. By controlling the silicon-based particle content within the negative electrode active material to a predetermined range, it is possible to achieve both the capacity per gram of the negative electrode active material and cycle stability, thereby improving the energy density and cycle performance of the battery. Selectively, the silicon-based particle content may be 30 wt% to 50 wt% based on the mass of the negative electrode active material. By using this condition, it is possible to further achieve both the capacity per gram of the negative electrode active material and cycle stability, thereby improving the energy density and cycle performance of the battery.
[0056] In some embodiments of this application, the porosity of the porous carbon framework layer 20 may be 40% to 70%, for example, 43%, 46%, 49%, 52%, 55%, 58%, 61%, 64%, 67%, or any of the above values within a given range. Increasing the porosity of the porous carbon framework layer is advantageous in improving the uniformity of the dispersion of silicon-based particles in the porous carbon framework layer, and on the other hand, it is advantageous in increasing the amount of silicon deposited inside the negative electrode active material and improving the inhibitory effect of the porous carbon framework layer on the expansion of silicon-based particles. Decreasing the porosity of the porous carbon framework layer is advantageous in reducing the effect of lithium supply on the overall strength of the negative electrode active material and reducing the risk of the overall structure collapsing. By controlling the porosity of the porous carbon framework layer within a predetermined range, it is also possible to improve the capacity per gram and cycle stability of the negative electrode active material while ensuring the overall strength of the negative electrode active material, thereby improving the energy density and cycle performance of the battery.
[0057] In some embodiments of this application, the pore size of the porous carbon framework layer 20 may be 1 nm to 50 nm, for example, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, or any of the above values within a given range. Increasing the pore size of the porous carbon framework layer not only reduces the difficulty of silicon depositing inside the negative electrode active material, particularly in the pores of the porous carbon framework layer, but is also advantageous in improving the inhibitory effect of the porous carbon framework layer on the expansion of silicon-based particles. At the same time, by keeping the pore size of the porous carbon framework layer below a predetermined range, it is also advantageous in improving the uniformity of the dispersion of silicon-based particles in the porous carbon framework layer. Controlling the pore size of the porous carbon framework layer within a predetermined range is further advantageous in improving the capacity per gram and the stability of the cycle structure of the negative electrode active material, thereby improving the energy density and cycle performance of the battery.
[0058] In some embodiments of this application, the Dv50 particle size of the negative electrode active material may be 10 μm or less (for example, 9 μm, 8 μm, 7 μm, 6 μm, 5 μm, 4 μm, 3 μm, etc. or less, or within a range of any of the above values), and the Dv90 particle size of the negative electrode active material may be 20 μm or less (for example, 18 μm, 17 μm, 15 μm, 14 μm, 13 μm, 12 μm, 11 μm, 10 μm, 9 μm, 8 μm, 5 μm, etc. or less, or within a range of any of the above values). The Dv50 and Dv90 particle sizes of the negative electrode active material can be measured by a laser particle size distribution analyzer (e.g., Malvern Master Size 3000) in accordance with standard GB / T 19077.1-2016. By keeping the particle size of the negative electrode active material within a low range, it is advantageous to reduce the risk that the particle size of the negative electrode active material is too large, which can easily hinder the transport of active ions, such as lithium ions, and thus affect battery performance. Furthermore, by controlling the Dv50 and Dv90 particle sizes of the negative electrode active material within a predetermined range, it is advantageous to improve the conductivity of the negative electrode sheet and enhance the improvement effect on battery performance. In addition, the Dv50 particle size of the negative electrode active material may be 1 μm or larger, and the Dv90 particle size may be 3 μm or larger. By ensuring that the particle size of the negative electrode active material satisfies predetermined conditions, it is advantageous to avoid the occurrence of many side reactions with the electrolyte due to the particle size of the negative electrode active material being too small, which would affect the improvement effect on battery performance.
[0059] In some embodiments of this application, the thickness of the carbon coating layer 30 may be 1 μm or less, for example, 0.02 μm, 0.05 μm, 0.08 μm, 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6 μm, 0.65 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, etc., or it may be within a range of any of the above values. Regarding the thickness of the carbon coating layer, in accordance with JY / T010-1996, the cross-section of the negative electrode active material particles may first be polished, the cross-sectional structure observed to confirm the components within the region, and then coating thickness data may be obtained. Specifically, the layered boundaries of the particle cross-section are observed from the polished cross-sectional morphology (CP morphology) of the negative electrode active material particles, and the thickness of the outermost coating layer of the particle is observed using a transmission electron microscope. The data can then be obtained by selecting different positions of the particle within the center of the field of view, recording the values, and calculating the average value. By providing a carbon coating layer, the volume expansion of silicon-based particles during charge-discharge cycles can be further suppressed, while the conductivity of the negative electrode active material can be improved. Increasing the thickness of the carbon coating layer is advantageous in improving the conductivity of the negative electrode active material and the suppression effect on the volume expansion of silicon-based particles during charge-discharge cycles. Decreasing the thickness of the carbon coating layer is advantageous in reducing the potential effect of lithium replenishment on the capacity per gram of the entire negative electrode active material, while limiting the ion desorption / insertion function of the carbon coating layer. Because the carbon coating layer exhibits a large ion insertion / desorption function, the capacity decay of the negative electrode active material tends to be rapid, which in turn negatively affects the improvement effect on the cycle stability of the negative electrode active material and reduces the risk of affecting the dynamic performance and cycle performance of the battery. By controlling the thickness of the carbon coating layer within a predetermined range, the capacity per gram of the negative electrode active material can be improved, as well as the conductivity of the negative electrode active material and the volume expansion associated with the charge-discharge cycle process can be improved.Selectively, the thickness of the carbon coating layer 30 may be 0.2 μm or less, more selectively, 0.1 μm or less, and even more selectively, 0.05 μm to 0.08 μm. By further controlling the thickness of the carbon coating layer within a predetermined range, it is possible to further consider the capacity per gram of the negative electrode active material, volume stability during the charge-discharge process, conductivity, and cycle life.
[0060] In some embodiments of this application, the particle size of the carbon core 10 may be 1 μm to 5 μm, for example, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, etc., or within any range of the above values. The particle size of the carbon core can be obtained by observing the cross-sectional morphology of the particles, recording and counting the particle size values of the particles within the field of view, and calculating the average value. By controlling the particle size of the carbon core to a predetermined range based on the particle size of the negative electrode active material and the thickness of the carbon coating layer, it is possible to further achieve both the overall structural stability of the negative electrode active material and the capacity per gram, and to improve the conductivity of the negative electrode active material and the volume expansion associated with the charge-discharge cycle process.
[0061] In some embodiments of this application, the carbon core may comprise one or more of graphite, porous carbon, and mesocarbon microbeads (MCMBs). Using graphite, porous carbon, and mesocarbon microbeads as the material for the carbon core is advantageous for the insertion and removal of active ions (e.g., lithium ions), and is advantageous for improving cycle performance and fast charging capability. Here, graphite may comprise artificial graphite and / or natural graphite, and selectively artificial graphite. Porous carbon may comprise, but is not limited to, hard carbon, and hard carbon may comprise, but is not limited to, carbon black, resin (e.g., phenolic resin), and / or pyrolysis carbon obtained from other organic polymers as precursors. Selectively, porous carbon may comprise hard carbon, which has a relatively higher specific capacity compared to graphite and mesocarbon microbeads, and using hard carbon as the carbon core is advantageous for further increasing the capacity per gram of negative electrode active material and improving the energy density of the battery.
[0062] In some embodiments of this application, the carbon precursor material used to form the porous carbon skeleton layer and the carbon coating layer is not particularly limited and can be flexibly selected by those skilled in the art according to their actual needs. For example, it is understood that the carbon precursor material used to form the porous carbon skeleton layer and the carbon coating layer may each independently comprise one or more of pitch, resin, soluble starch, sucrose, glucose, and polyacrylic acid esters.
[0063] In some embodiments of this application, as shown in Figure 2, the negative electrode active material may further include a carbon core coating layer 11 in the containment space, which covers at least a portion of the outer surface of the carbon core 10. Here, a wave-absorbing material may be distributed in the carbon core coating layer 11. By setting it in this way, a central heat field can be formed on the surface of the carbon core during manufacturing, improving the wave-absorbing effect throughout the interior of the negative electrode active material, further promoting silicon deposition throughout the interior of the negative electrode active material, reducing the silicon content on the surface of the negative electrode active material, and improving the suppressive effect of the negative electrode active material on the volume expansion of silicon-based particles during the charge-discharge cycle process.
[0064] In some embodiments of this application, the mass ratio of the wave-absorbing material to the carbon core coating layer 11 may be greater than the mass ratio to the porous carbon skeleton layer 20. In the manufacturing process of the negative electrode active material, this structure helps to preferentially heat the interior, resulting in a higher internal temperature than the exterior. This is advantageous because silicon deposits first in the interior and gradually spreads outwards, resulting in a distribution where the silicon content gradually decreases from the interior to the exterior. This allows for the further deposition of more silicon inside the porous carbon skeleton layer, and the amount of silicon deposited on the side of the porous carbon skeleton layer closer to the carbon core is greater than the amount of silicon deposited on the side closer to the carbon coating layer. Thus, on the one hand, it is advantageous to further reduce the silicon content on the surface of the negative electrode active material, and on the other hand, it is advantageous to further improve the improvement effect of the porous carbon skeleton layer and carbon coating layer on the volume effect of silicon-based particles. Both of these are advantageous in improving the structural stability of the negative electrode active material during cycling and improving the energy density and cycle performance of the battery.
[0065] In some embodiments of this application, the thickness of the carbon core coating layer 11 may be 1 μm or less, for example, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, etc., or it may be within a range of any of the above values. The thickness of the carbon core coating layer can be obtained by vacuum cutting the material with an Ar ion beam, directly observing the cross-sectional shape, identifying the layered material on the surface of the carbon core, selecting particles, measuring the thickness at multiple points, and calculating the average value. By controlling the thickness of the carbon core coating layer to a predetermined range, it is possible to promote the deposition of more silicon throughout the interior of the anode active material, improve cycle performance, and further secure the total capacity per gram of the anode active material. Selectively, the thickness of the carbon core coating layer 11 may be 0.3 μm to 1 μm, and more selectively, 0.3 μm to 0.5 μm.
[0066] In some embodiments of this application, the resistivity of the negative electrode active material at room temperature and under a pressure of 4 MPa may be between 100 mΩ·cm and 10,000 mΩ·cm, for example, 100 mΩ·cm, 120 mΩ·cm, 150 mΩ·cm, 200 mΩ·cm, 250 mΩ·cm, 300 mΩ·cm, 350 mΩ·cm, 400 mΩ·cm, or any range of the above values. The resistivity of the negative electrode active material can be measured using a powder resistivity and pressure density meter (for example, model PRCD2100 manufactured by Yuanneng Technology). The specific operation may include weighing a certain mass of sample at room temperature, adjusting the depth of the feed chamber, feeding the sample into the feed chamber, applying pressure, manually collecting data, and recording the resistivity measurement results of the sample powder at different pressure points. In embodiments of this application, the resistivity of the sample powder under 4 MPa may be recorded and considered in particular. By improving the ionic conductivity of the negative electrode active material, the dynamic performance of the negative electrode active material can be further improved. Selectively, the resistivity of the negative electrode active material at room temperature and a pressure of 4 MPa may be between 100 mΩ·cm and 300 mΩ·cm. By controlling the resistivity of the negative electrode active material within a predetermined range, its volume effect and cycle performance can be improved, and its dynamic performance can be further enhanced.
[0067] A second aspect of this application provides a method for producing a negative electrode active material as described in the first aspect of this application. The production method includes the steps of: mixing a carbon core material, a pore-forming agent, a carbon skeleton precursor material, and a solvent to obtain a first mixture; mixing a wave-absorbing material with the first mixture to obtain a second mixture; applying spray molding and fluid drying treatment to the second mixture to obtain composite particles; applying carbonization treatment and activation treatment to the composite particles to obtain skeleton particles in which the carbon core is coated with a porous carbon skeleton layer; applying microwave heating to the skeleton particles and introducing a gas-phase silicon source to deposit silicon to obtain precursor particles; and coating at least a portion of the outer surface of the precursor particles with a carbon coating layer to obtain a negative electrode active material.
[0068] In contrast to the problems inherent in conventional heat treatment processes for negative electrode active materials, such as the difficulty in controlling the finished state of silicon-carbon composite materials, the high required temperatures, long sintering times, and high energy consumption, as well as the difficulty of silicon penetrating the carbon framework, which results in a large number of silicon crystal particles on the material's surface, causing serious expansion problems during battery cycling, directly affecting the structural stability of silicon-based materials, and ultimately impacting cycle performance, the embodiments of this application, by adding a wave-absorbing material during manufacturing, generate heat by combining the wavelength range of the wave-absorbing material with the basic microstructure of the material, allowing for precise heating of specific locations within the material. This also offers advantages such as a rapid heating rate, high energy utilization rate, high heating efficiency, safety, hygiene, and no contamination. Furthermore, compared to the conventional heat transfer process from the outside to the inside, the self-heating method of the wave-absorbing material, which heats the entire material without a gradient, and the rapid heating rate effectively reduce heating temperature and time, increasing production rate, reducing costs, and improving product quality. More importantly, it is possible to deposit more silicon in the deeper parts of the pores of the porous carbon skeleton layer, effectively suppressing the volume expansion of silicon and maintaining the structural stability of silicon-based particles during long-term cycles. Furthermore, by forming an additional carbon coating layer to obtain a core-shell composite structure, the structures of each layer can be made to interact, further suppressing the expansion of internal silicon-based particles and improving the battery's cycle performance. As described above, the method for manufacturing the negative electrode active material in this application has the beneficial effect of allowing the manufacturing process to be controlled, enabling precise heating using wave-absorbing materials and microwave heating to achieve a silicon orientation distribution and obtain a negative electrode active material with a desired structure. Moreover, it is advantageous in reducing the heating temperature and heating time during manufacturing, thereby increasing manufacturing efficiency and reducing costs. In addition, the manufactured negative electrode active material effectively suppresses the volume expansion of silicon and improves its structural stability during cycles.
[0069] In some embodiments of this application, a carbon core material (e.g., a hard carbon material) is mixed with a pore-forming agent, a carbon skeleton precursor material (e.g., a phenolic resin), and a solvent (e.g., selectively volatile solvent) to obtain a first mixture. In this process, the carbon skeleton precursor material and the carbon core material are mixed, which is advantageous for the formation of a porous carbon skeleton layer on the surface of the carbon core material in a later stage. Selectively dissolving the carbon skeleton precursor material and the pore-forming agent sufficiently in the solvent is even more advantageous for forming a porous carbon skeleton layer on the surface of the carbon core material. By adding a pore-forming agent, a porous structure can be formed in the carbon skeleton layer formed in a later stage, which is advantageous for silicon deposition in the later stage. The specific types of pore-forming agents and solvents are not particularly limited as long as they can achieve the desired effect, and those skilled in the art can understand that they can be flexibly selected according to their actual needs. For example, the pore-forming agent may include one or more of sodium chloride, potassium chloride, zinc chloride, sodium carbonate, potassium carbonate, zinc carbonate, zinc acetate, and ammonium acetate, and the solvent may include, but is not limited to, water and / or alcohol. For example, the solvent may be a mixture of water and alcohol, i.e., an alcohol solution, and the alcohol may include, but is not limited to, methanol, ethanol, ethylene glycol, polyethylene glycol, glycerol, isopropyl alcohol, or polyhydric alcohol. As a specific example, a first mixture may be obtained by thoroughly mixing a hard carbon material, a phenolic resin, zinc chloride, and an aqueous ethanol solution. Furthermore, the relative amounts used for the carbon core material and the carbon skeleton precursor material can be flexibly selected according to actual circumstances such as the expected dimensions of the core-shell structure of the negative electrode active material and the type of core-shell material, and are not particularly limited here. Relevant characteristics such as the type of carbon core material, particle size, and type of carbon skeleton precursor material have already been described in the preamble, and a redundant explanation is omitted here.
[0070] In some embodiments of this application, the mass ratio of the porosizing agent to the carbon skeleton precursor material may be (10~1):(1~100), for example, 5 / 1, 3 / 1, 2 / 1, 1.5 / 1, 5 / 4, 1 / 1, 0.5 / 1, 2 / 5, 1 / 3, 1 / 2, 1 / 5, 1 / 10, 1 / 15, 1 / 20, 1 / 30, 1 / 40, 1 / 50, 1 / 60, 1 / 70, 1 / 80, 1 / 90, or any of the above values within a range. The amount of porosizing agent used has a certain degree of influence on the porosity and pore size of the finally formed porous carbon skeleton layer, and controlling the amount of porosizing agent used within a predetermined range may be even more advantageous in obtaining a porous carbon skeleton layer with a desired porosity and micro-mesoporous porous structure. Selectively, the mass ratio of the porosity agent to the carbon skeleton precursor material may be (10~1):(2~10), for example 1:(2~10), and even more selectively, (10~1):(2~5), for example 1:(2~5). This may be advantageous in improving the porosity and pore size of the carbon skeleton layer, optimizing the distribution and deposition of silicon within the anode active material, and the expansion suppression effect of the silicon-based particles by the overall structure of the anode active material, thereby further improving the capacity per gram and cycle performance of the anode active material.
[0071] In some embodiments of this application, the sum of the mass ratio of the pore-forming agent and the mass ratio of the carbon skeleton precursor material in the first mixture may be 10 wt% to 70 wt%, for example, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, etc., or it may be within any range of the above values. In the actual manufacturing process, based on the structure of the anode active material, it is desirable that the amount of carbon core material used is less than that of the carbon skeleton precursor material, and that the porous carbon skeleton layer can be easily formed. This is achieved by ensuring that the pore-forming agent and the carbon skeleton precursor material are completely soluble in the solvent. Furthermore, by ensuring that the mass ratio of the pore-forming agent and the mass ratio of the carbon skeleton precursor material in the first mixture are within a predetermined range, it is even more advantageous to form a porous carbon skeleton layer on the surface of the carbon core. Additionally, by adjusting the mass ratio of the pore-forming agent and the mass ratio of the carbon skeleton precursor material in the first mixture, the thickness of the porous carbon skeleton layer can be flexibly controlled, which is even more advantageous in obtaining an anode active material with desired structural dimensions.
[0072] In some embodiments of this application, in the process of mixing the wave-absorbing material with the first mixture to obtain the second mixture, the particle size of the wave-absorbing material can be made nanoscale. For example, Fe3O4 nanoparticles may be mixed with the first mixture. By selecting a nanoscale wave-absorbing material for a carbon core material with micrometer-scale dimensions, it is advantageous not only to distribute a larger amount of the wave-absorbing material in the carbon skeleton layer formed later, but also to improve the uniformity of its distribution in the carbon skeleton layer. Furthermore, because the particle size of the nanoparticles is small, it is possible to improve the surface activity of the wave-absorbing material and enhance its wave-absorbing performance. For the purposes of this explanation, the amount and type of wave-absorbing material used have already been described in the negative electrode active material described in the first embodiment of this application, and a redundant explanation will be omitted here.
[0073] In some embodiments of this application, before preparing the first mixture, the process may further include coating at least a portion of the outer surface of the carbon core material with a carbon core coating layer in which a wave-absorbing material is distributed. For example, the wave-absorbing material or a wave-absorbing material precursor material may be deposited on the surface of the carbon core material by a liquid-phase method and formed by a related post-processing process. For example, taking the case where Fe3O4 is used as the wave-absorbing material for the carbon core coating layer, an alkaline dispersion may be obtained by mixing the carbon core material, a soluble alkali salt, and water. Subsequently, the mixture may be mixed with a soluble iron salt and subjected to a hydrothermal reaction and heat treatment to form a carbon core coating layer on the surface of the carbon core material that is similar in structure to a porous carbon skeleton layer. Here, after mixing the alkaline dispersion with the wave-absorbing material or a wave-absorbing material precursor material to obtain a carbon core coating layer that is similar in structure to a porous carbon skeleton layer, post-processing may be performed according to the actual circumstances.
[0074] As one specific example, when forming a carbon core coating layer, the carbon core material (e.g., hard carbon) may be ultrasonically dispersed in deionized water, and the mixture may be adjusted to be weakly alkaline by adding NaOH. For example, the pH of the mixture may be selectively adjusted to about 9, or 9±1. Then, a trivalent iron salt and / or its hydrate (e.g., FeCl3·6H2O) may be added, and low-temperature ultrasonic dispersion may be continued until uniform dispersion is achieved. After that, a reducing agent (e.g., hydrazine hydrate) may be added to carry out a hydrothermal reaction. After that, the reaction product may be washed by cooling, baked, and sintered under a nitrogen atmosphere to obtain a carbon core having a porous coating layer containing the wave-absorbing material Fe3O4. Here, sintering under a nitrogen atmosphere effectively avoids or suppresses the problem that the carbon core material is sensitive to oxygen and prone to oxidation ablation at high temperatures. Furthermore, regarding Fe3O4, by using a soluble iron salt as a precursor to form the wave-absorbing material Fe3O4, the uniformity of the dispersion of the wave-absorbing material on the surface of the carbon core can be further improved, which is advantageous for obtaining wave-absorbing materials with nanoparticle sizes. It should be noted that the specific operational procedures and control process parameters for controlling the formation of the carbon core coating layer on the surface of the carbon core material can be flexibly selected according to actual needs, such as the type of wave-absorbing material chosen, and are not particularly limited here. Furthermore, other relevant features and effects of forming a carbon core coating layer containing wave-absorbing material on the surface of the carbon core material have already been described in the preceding paragraph, and redundant explanations will be omitted here.
[0075] In some embodiments of this application, when forming a carbon core coating layer on the surface of the carbon core material, the mass ratio of the wave-absorbing material to the carbon core material may be 1:(5~20), for example, 1 / 6, 1 / 7, 1 / 8, 1 / 9, 1 / 10, 1 / 11, 1 / 12, 1 / 13, 1 / 14, 1 / 15, 1 / 16, 1 / 17, 1 / 18, 1 / 19, or any of the above values within a given range. By controlling the amount of wave-absorbing material used in the carbon core coating layer to a predetermined range, on the one hand, it is possible to provide sufficient wave-absorbing material in the carbon core coating layer on the surface of the carbon core material, allowing more silicon to be deposited in the depths of the pores of the porous carbon skeleton layer. On the other hand, when the amount of wave-absorbing material used is excessive, it is advantageous to avoid aggregation into large molecules on the surface of the carbon core material, which would further affect the dispersion uniformity and wave-absorbing effect of the wave-absorbing material on the surface of the carbon core material. This further promotes uniform orientation deposition of silicon and improves the cycle performance of the negative electrode active material.
[0076] In some embodiments of this application, in the process of spray molding and fluid drying of the second mixture, and then carbonization and activation treatment of the resulting composite particles, the specific process conditions for controlling the spray molding, fluid drying, carbonization, and activation treatments can be flexibly selected according to actual needs and are not particularly limited to the embodiments of this application. For example, the second mixture can be atomized and cured under conditions of 100°C or higher to form spherical particles, and then proceeded to a fluid drying step to stabilize the resin surface and reduce adhesion between particles. Subsequently, the collected spherical particles are subjected to sintering carbonization treatment, and then the sintered carbonized product is activated by passing superheated steam through them. Selectively, the temperature of the carbonization treatment may be 700°C to 1600°C, and the temperature of the activation treatment may be 700°C to 1200°C, and the time may be selectively 0.5h to 10h. By controlling the conditions of the carbonization treatment and activation treatment within a predetermined range, the formation of a composite structure in which the carbon core is covered with a porous carbon skeleton layer can be further promoted.
[0077] In some embodiments of this application, when microwave heating is performed on skeletal particles and silicon is deposited by introducing a gas-phase silicon source, the frequency setting range and heating time of the microwave treatment can be flexibly selected according to the type of wave-absorbing material. For example, the microwave frequency range may be set to 8.0 GHz to 12.4 GHz to achieve fixed-point heating, with an absorptivity range of 12 dB to 16 dB, where the wave-absorbing material absorbs wavelengths within this frequency band and converts them into thermal energy, and the heating time is adjusted based on the amount of silicon deposited. Furthermore, the specific type of gas-phase silicon source is not particularly limited here and can be flexibly selected according to actual needs, for example, it may be a gas-phase silane. In addition, the microwave heating time and the flow rate of the gas-phase silicon source per unit time can be flexibly adjusted based on the desired amount of silicon deposited inside the negative electrode active material.
[0078] In some embodiments of this application, when forming a carbon coating layer on the surface of precursor particles obtained by depositing silicon by microwave heating, the precursor particles and a carbon coating layer precursor material (e.g., pitch) are mixed and heat-treated to obtain a negative electrode active material in which at least a portion of the outer surface of the precursor particles is coated with a carbon coating layer. When selectively forming the carbon coating layer, the heat treatment temperature may be 800°C to 1150°C, and the time may be 1 to 5 hours. It should be noted that the coating used when mixing the precursor particles and the carbon coating layer precursor material may be a pitch coating, a resin coating, or a coating by vapor phase CVD, and the relative amounts used of precursor particles and carbon coating layer precursor material can be flexibly selected according to the actual situation such as the desired structural dimensions of the negative electrode active material, and are not particularly limited here.
[0079] A third aspect of this application provides a negative electrode sheet. The negative electrode sheet comprises a negative electrode active material manufactured by the negative electrode active material described in the first aspect of this application and / or the negative electrode active material manufacturing method described in the second aspect of this application. For the purposes of this explanation, the features and effects described for the negative electrode active material described in the first aspect of this application and the negative electrode active material manufacturing method described in the second aspect of this application also apply to the negative electrode sheet, and redundant explanations are omitted here. In summary, the negative electrode sheet has greater structural stability during the charge-discharge cycle process and is advantageous in reducing safety risks such as battery swelling.
[0080] In some embodiments of this application, the negative electrode sheet may include a negative electrode current collector and a negative electrode active material layer provided on at least one layer of the negative electrode current collector. The active material in the negative electrode active material layer may be partially or entirely the negative electrode active material described in the first embodiment of this application. In addition to the active material, the negative electrode active material layer may also contain a conductive agent and a binder. Here, the relative amounts used of the active material, conductive agent, and binder, the content of the negative electrode active material described in the first embodiment of this application, the specific types of conductive agent and binder, the material of the negative electrode current collector, the thickness of the negative electrode active material layer, the pressure density or surface density, etc., can be flexibly selected according to the actual situation and are not particularly limited here.
[0081] A fourth aspect of this application provides a battery comprising a negative electrode active material manufactured by the method for manufacturing the negative electrode active material described in the first aspect of this application and / or the method for manufacturing the negative electrode active material described in the second aspect of this application and / or a negative electrode sheet described in the third aspect of this application. Optionally, the battery may be a secondary battery. Further optionally, the battery may be a lithium-ion battery.
[0082] Compared to conventional batteries, using the negative electrode active material described in the first aspect of this application, the negative electrode active material manufactured by the method for manufacturing the negative electrode active material described in the second aspect of this application, or the negative electrode sheet described in the third aspect of this application is advantageous in improving the battery's cycle performance and energy density. Furthermore, the features and effects described for the negative electrode active material described in the first aspect of this application, the method for manufacturing the negative electrode active material described in the second aspect of this application, and the negative electrode sheet described in the third aspect of this application are similarly applicable to the battery described in the fourth aspect of this application, and it is understandable that redundant explanations are omitted here.
[0083] Furthermore, in addition to the negative electrode sheet, the battery generally includes a positive electrode sheet, a separator, an electrolyte, and a case assembly, where the sheet, separator, and electrolyte are housed in a cavity formed by the case assembly. Depending on the type of battery, the case assembly may be made of aluminum plastic film or a metal case assembly, and the metal case assembly may include a rectangular case assembly and a cylindrical case assembly. Regardless of the type of battery, if the battery includes the negative electrode active material described in the first aspect of this application and / or the negative electrode active material manufactured by the method for manufacturing the negative electrode active material described in the second aspect of this application, and / or the negative electrode sheet described in the third aspect of this application, it can be understood to fall within the technical scope of the battery described in the fourth aspect of this application. Here, the characteristics of the negative electrode sheet have already been described in the preamble, and a redundant explanation is omitted here. The structure and composition of the positive electrode sheet, the specific material and type of the separator may be those common in the art, and the composition of the electrolyte may be a composition common in the art, and those skilled in the art can flexibly select according to their actual needs.
[0084] In some embodiments of this application, the battery may be a stacked battery or a wound battery, and the wound battery may be a rectangular battery (shown in Figure 3), a cylindrical battery, or any other shape. Depending on the type of battery, the positive electrode sheet, negative electrode sheet, and separator may be stacked and arranged to form a stacked unit, or they may be stacked and then wound to form a wound body.
[0085] In some embodiments of this application, the battery may be a battery cell 1 (see Figure 3), or a battery module 2 (see Figure 4) or battery pack 3 (see Figure 5) composed of a battery cell 1.
[0086] In some embodiments of this application, the battery may be a battery module, and the number of battery cells contained in the battery module may be one or more, and the specific number can be adjusted according to the application and capacity of the battery module. Figure 4 is an example of a battery module 2. As shown in Figure 4, in the battery module 2, a plurality of battery cells 1 may be arranged sequentially along the longitudinal direction of the battery module 2. Of course, they may be arranged in any other way. Furthermore, the plurality of battery cells 1 may be fixed with fasteners. Optionally, the battery module may further include a packaging assembly having a housing space, the packaging assembly may include a bottom plate, side plates and a lid plate, and the plurality of battery cells 1 are housed in the housing space.
[0087] In some embodiments of this application, the battery modules may be assembled as a battery pack, and the number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack. As shown in Figures 5 and 6 (Figures 5 and 6 show a battery pack 3 as an example), the battery pack 3 may include a battery box and a plurality of battery modules 2 provided inside the battery box. The battery box may include an upper box 4 and a lower box 5, and the upper box 4 can cover the lower box 5 to form a sealed space for housing the battery modules 2. The plurality of battery modules 2 may be arranged inside the battery box in any way.
[0088] Furthermore, this application provides an electrical device comprising a negative electrode active material described in the first aspect of this application, and / or a negative electrode active material manufactured by a method for manufacturing a negative electrode active material described in the second aspect of this application, and / or a negative electrode sheet described in the third aspect of this application, and / or a battery described in the fourth aspect of this application.
[0089] The aforementioned battery, for example, a cell, battery module, or battery pack, may be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), trains, ships and satellites, and energy storage systems. As shown in Figure 7, the electrical device may, in specific examples, be a vehicle.
[0090] An electrical device may select a specific type of battery according to its usage needs, for example, a cell, a battery module, or a battery pack.
[0091] For example, the electrical device may be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. A battery pack or battery module may be used to meet the electrical device's demands for high power output and high energy density of batteries.
[0092] As another example, the electrical device may be a mobile phone, tablet PC, or laptop computer. The electrical device is usually required to be thin and may use a cell as its power source.
[0093] The following describes embodiments of this application. The embodiments described below are illustrative and are for illustrative purposes only, and should not be understood as limiting this application. Where the specific technology or conditions described in the embodiments are not explicitly stated, they are carried out in accordance with the technology or conditions described in the literature in the art or in the specifications of the products. Reagents and equipment used where the manufacturer is not specified are all common products that are commercially available.
[0094] Example 1 (1) Manufacturing of positive electrode sheets Lithium iron phosphate as the positive electrode active material, acetylene black as the conductive agent, and polyvinylidene fluoride (PVDF) as the binder were mixed in a mass ratio of 96:2:2. N-methylpyrrolidone (NMP) was added as the solvent, and the mixture was stirred with a vacuum mixer until the reaction system was homogeneous to obtain a positive electrode slurry. The positive electrode slurry was uniformly applied to both sides of an aluminum foil positive electrode current collector with a thickness of 12 μm, dried at 115°C for 15 min, and cold-pressed. The thickness of the positive electrode active material layer on one side was 84 μm. A positive electrode sheet with a length of 605 mm and a film width of 88 mm was obtained by slitting, and the coating weight on one side was 20 mg / cm². 2 The positive electrode active material layer has a pressure density of 2.4 g / cm³. 3 That was the case.
[0095] (2) Manufacturing of negative electrode active material and negative electrode sheet (i) Synthesis of negative electrode active material (a) 50 g of hard carbon particles Dv50 with a diameter of 3 μm was weighed and dispersed in 1000 g of anhydrous ethanol. Then, 500 g of phenolic resin and 500 g of anhydrous zinc chloride (Aladdin Biochemical) were added and the mixture was stirred until a homogeneous composite resin dilute solution was obtained.
[0096] (b) 16 g of Fe3O4 nanopowder (average particle size 20 nm) was added to the above solution, and after sonication for 30 mins, a homogeneous dispersion was obtained.
[0097] (c) Furthermore, the dispersion was atomized and cured at 150°C using a spray molding process to form spherical resin particles, which were then subjected to fluid drying.
[0098] (d) Stabilized spherical resin particles were collected, heated to 1000°C at a rate of 2°C / min, and kept warm for 2 hours to perform carbonization treatment. Subsequently, the carbonized material was activated for 2 hours by passing superheated steam through it at 800°C with a water supply rate of 2 L / min.
[0099] (e) The carbon material obtained by the activation treatment was heated with microwaves, the frequency band range of the microwave treatment was set to 8 GHz to 12.4 GHz, and when the temperature of the reaction system reached 500°C, it was thermally decomposed by passing silane gas through it to perform silicon deposition treatment.
[0100] (f) Furthermore, the material obtained above was mixed with pitch, and the amount of pitch used was set to 5 wt% of the mass of the material obtained in step (e). After heat treatment at 1150°C for 1 hour, a silicon-carbon composite anode active material was obtained, which included a carbon core, a porous carbon skeleton layer in which wave-absorbing material and silicon-based particles are distributed in the pores, and a carbon coating layer, in that order from the inside out.
[0101] (ii) Manufacturing of negative electrode sheets The negative electrode active material (25 wt% silicon-carbon composite negative electrode active material produced in step (i) above + 75 wt% artificial graphite), conductive carbon black, sodium carboxymethylcellulose (CMC-Na) as a thickener, and styrene-butadiene rubber (SBR) emulsion as a binder are thoroughly mixed in an appropriate amount of deionized water in a weight ratio of 96.5:1.0:1.0:1.5 to form a uniform negative electrode slurry. This slurry is then applied to both sides of the copper foil of the negative electrode current collector, which is 8 μm thick. After processes such as baking, the thickness of the negative electrode active material layer on one side is 50 μm, and the surface density on one side is 8 mg / cm². 2 A negative electrode sheet is obtained, and the pressure density of the negative electrode active material layer is 1.6 g / cm³. 3 That was the case.
[0102] (3) Preparation of electrolyte Ethylene carbonate (EC), ethylmethyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a 1:1:1 volume ratio to obtain an organic solvent. A thoroughly dried lithium salt, LiPF6, was dissolved in the organic solvent to achieve a lithium salt concentration of 1 mol / L, and the mixture was homogeneously mixed to obtain an electrolyte.
[0103] (4) Manufacturing of separators A 12μm thick polyethylene film was selected as the separator.
[0104] (5) Manufacturing of secondary batteries The positive electrode sheet, separator, and negative electrode sheet described above were stacked in this order such that the separator acts to separate the positive and negative electrode sheets. A lithium foil was placed on the surface of the non-reactive region and wound to obtain a bare cell. The bare cell was placed in an outer case and dried. Then, an electrolyte solution was injected at an injection coefficient of 4.2 g / Ah, and after processes such as vacuum packaging, standing, chemical conversion, and molding, a secondary battery with a capacity of approximately 3 Ah was obtained.
[0105] Example 2 The differences from Example 1 are as follows: When synthesizing the negative electrode active material in (i), step (a) is performed. (a-1) Disperse 50g of hard carbon particles Dv50, which are 3μm in size, using ultrasonic waves in deionized water, and adjust the pH to 9 by adding NaOH. (a-2) Weigh 15g of FeCl3·6H2O and pour it into the dispersion obtained in (a-1), and continue low-temperature ultrasonic dispersion. (a-3) Add 5 ml of hydrazine hydrate to the mixture obtained in (a-2), stir quickly and uniformly, then pour into a hydrothermal reactor and heat at 140°C for 8 hours in a homogeneous reactor. (a-4) Cool to room temperature, wash the product in the reactor with ethanol and deionized water, filter, bake, place the product in a tubular furnace, raise the temperature to 400°C at a rate of 10°C / min under a nitrogen atmosphere, react for 1 hour, and obtain hard carbon with a wave-absorbing material coating layer on the surface. (a-5) The hard carbon obtained in step (a-4) is weighed out to 50 g, dispersed in 1000 g of anhydrous ethanol, and then 500 g of phenolic resin and 500 g of anhydrous zinc chloride (Aladdin Biochemical) are added and stirred until a homogeneous composite resin dilute solution is obtained.
[0106] Comparative Example 1 (i) differs from Example 1 in that step (b) is not included in the synthesis of the negative electrode active material, i.e., the wave-absorbing material Fe3O4 was not added during the production of the negative electrode active material.
[0107] Examples 3-8 In Example 1, the amount of Fe3O4 powder added in step (b) differed when synthesizing the negative electrode active material in (i), and the content of the wave-absorbing material Fe3O4 differed based on the mass of the manufactured negative electrode active material, as detailed in Table 1.
[0108] Examples 9-11 In Example 1, the average particle size of the wave-absorbing material Fe3O4 used in the synthesis of the negative electrode active material (i) was different, as detailed in Table 1.
[0109] Examples 12-14 In Example 2, when synthesizing the negative electrode active material (i), the amount of FeCl3·6H2O used in step (a-2) was different, resulting in a different thickness of the formed carbon core coating layer, as detailed in Table 1.
[0110] Examples 15-19 In Example 1, the type of wave-absorbing material used in the synthesis of the negative electrode active material (i) is different, as detailed in Table 1.
[0111] Examples 20-23 In Example 1, the amount of pitch used to form the carbon coating layer differed when synthesizing the negative electrode active material (i), resulting in a difference in the thickness of the formed carbon coating layer, as detailed in Table 1.
[0112] Examples 24-27 In Example 1, when synthesizing the negative electrode active material (i), the amount of pore-forming agent used in step (a) was different. Specifically, in step (a), the amount of phenol resin used was the same as in Example 1, but the amount of pore-forming agent used was changed, altering the mass ratio of the two. Details are shown in Table 1.
[0113] Performance testing of secondary batteries The secondary batteries manufactured in each of the above examples and comparative examples were subjected to rate charging performance tests and cycle performance tests, and the test methods included the following:
[0114] 1. Cycle performance test of secondary batteries In a 25°C environment, the battery was left standing for 5 minutes, discharged to 2.5V at 0.33C, left standing for 5 minutes, charged to 3.65V at 0.33C, charged at a constant voltage of 3.65V down to 0.05C, left standing for 5 minutes, and discharged to 2.5V at 0.33C. The capacity C0' at this time was recorded. After leaving the secondary battery standing for 5 minutes, it was moved to a 45°C environment, left standing for 20 minutes, charged to 3.65V at 1C, charged at a constant voltage of 3.65V down to 0.05C, left standing for 5 minutes, discharged to 2.5V at 1C, and left standing for 5 minutes. A charge-discharge cycle was performed according to this procedure. Discharge capacity C for each cycle m Record the number of cycles, where m indicates the number of cycles, and C m The battery was stopped until / C0' × 100% = 80%, and the value of m at this point was recorded as the cycle life of the secondary battery.
[0115] 2. Test of the rate of increase in the thickness of the negative electrode sheet. A pre-fabricated negative electrode sheet was prepared, and its thickness was measured at multiple points before winding (polymer film may be used). The average value was calculated and defined as d0. After assembling the secondary battery, it was left to stand in a 25°C environment until it reached a constant temperature. It was then charged with a constant current of 0.33C at 3.65V, then with a constant voltage of 3.65V until the current reached 0.05C, and then discharged at 0.33C at 2.5V. This process was repeated m times. After that, the battery was charged with a constant current of 0.33C at 3.65V, then with a constant voltage of 3.65V until the current reached 0.05C. The battery was then disassembled, the negative electrode sheet was removed, and after the surface of the negative electrode was dried, the measurement point positions of the negative electrode sheet before winding were determined (polymer film may be used). The thickness of the negative electrode sheet was measured again at multiple points, the average value was calculated and defined as d0. m Assuming that the rate of increase in the negative electrode sheet thickness after m cycles is (d m The result was -d0) / d0 × 100%.
[0116] 3. Measurement of the thickness of the carbon coating layer and core coating layer in the negative electrode active material. In accordance with JY / T010-1996, the following 1, 2, 3, and 4 were included: 1. Sample preparation. a) Mix the sample preparation binder (PVDF dispersed in NMP with an 8 wt% content) and the negative electrode active material particle powder uniformly in a 1:5 mass ratio, then coat the mixture onto copper foil and bake at 60°C for 30 mins to prepare for use; b) Cut the sample into 6 mm x 6 mm squares with scissors and attach it to the CP sample stage, ensuring that the sample protrudes within 1 mm from the sample stage; c) Cut the sample over 30 mins using a voltage of 7.5 kV (the balance point between efficiency and quality); and d) Determine whether or not gold plating is necessary on the sample depending on the strength of conductivity, with the time being approximately 60 seconds for the precursor. 2. Parameter setting. Mode: In-lens, Voltage: 10 kV, Aperture: 30 um, Working distance: 4.5 mm. 3. Measurement. Medium or large particles were targeted, and images were taken at three locations under 50K, 30K, 10K, 5K, 3K, 1K, and 500K. 4. Using a high-magnification graph, three particles in the central region of the measurement target area were selected, five reading points were chosen for each particle, and then the average value was calculated through statistical analysis.
[0117] 4. XRD test. This was performed in accordance with JIS K 0131-1996 (General rules for X-ray diffraction analysis).
[0118] The negative electrode active materials and secondary batteries produced in Examples 1-27 and Comparative Example 1 were tested under similar conditions, and the test results are shown in Table 1. The negative electrode active materials produced in Example 1 and Comparative Example 1 were subjected to XRD testing, and the results are shown in Figures 8-9. [Table 1-1] [Table 1-2]
[0119] The results and conclusions are as follows: Figures 8 and 9 show the XRD patterns of the anode active materials produced in Example 1 and Comparative Example 1, respectively. The strong diffraction peaks shown in the figures are all signals from silicon. As can be seen from the figures, the silicon peak is more pronounced in the anode active material produced in Comparative Example 1. Analysis revealed that the anode active material produced in Example 1 contains a wave absorber, which contributes to the distribution of silicon within the carbon bulk phase, and the silicon diffraction peak is covered by carbon. In contrast, in Comparative Example 1, silicon is not synthesized inside the bulk phase and is exposed on the carbon surface, resulting in a more pronounced silicon peak.
[0120] As can be seen from the test results in Examples 1 to 27, Comparative Example 1, and Table 1, the anode active material produced by the method according to the above examples of this application has a good improvement effect on anode expansion and cycle performance. Furthermore, compared to the case in which only a carbon coating layer is formed outside the porous carbon skeleton layer, simultaneously forming a carbon core coating layer containing a wave-absorbing material outside the carbon core is advantageous for further improving anode expansion and cycle performance. Moreover, by optimizing the type, amount, and particle size of the wave-absorbing material introduced into the anode active material, as well as the thickness of the carbon coating layer outside the porous carbon skeleton layer, the thickness of the core coating layer, and the relative amounts used of the porosizing agent and carbon skeleton precursor, excellent cycle stability and cycle life can be further obtained. Overall, as the mass percentage of the wave-absorbing material in the negative electrode active material increases, the improvement effect on the cycle stability and cycle life of the negative electrode active material increases before decreasing. Considering cost, energy density, etc., the mass percentage of the wave-absorbing material in the negative electrode active material is selectively 10 wt% or less. Furthermore, while increasing the thickness of the carbon coating layer can significantly improve the volume expansion of the negative electrode active material, it may decrease the cycle life. Analysis revealed that if the carbon coating layer is too thick, the ion transfer pathway becomes too long, and insertion and deinsertion occur only within the carbon coating layer. This is because too many ions can occur, potentially leading to a rapid decrease in cycle life. Therefore, the thickness of the carbon coating layer should be selectively set to 1 μm or less, and even more selectively to 0.1 μm or less. Furthermore, the relative amounts of porosizing agents and carbon skeleton precursors used during the production of the anode active material can have a certain degree of influence on the volume expansion and cycle life improvement effect of the anode active material. Analysis has shown that the relative amounts of both affect the porosity of the porous carbon skeleton layer, and may further affect the proportion of wave-absorbing material in the anode active material and the cycle performance of the anode active material.
[0121] Finally, the following should be explained: The above embodiments are merely for illustrative purposes and do not limit the technical solutions of this application. Although this application has been described in detail with reference to the embodiments described above, those skilled in the art should understand that they may modify the technical solutions described in the embodiments described above, or make equivalent substitutions to some or all of their technical features, and that such modifications or substitutions will not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application, and will all be included within the scope of the claims and specification of this application. In particular, as long as there is no structural inconsistency, any of the technical features described in each embodiment can be combined in any manner. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions included in the claims. [Explanation of Symbols]
[0122] 1 Secondary battery 2 Battery Modules 3 Battery pack 4. Top box 5 Lower box 10 Carbon core 11. Carbon core coating layer 20 Porous carbon skeleton layer 30. Carbon coating layer.
Claims
1. Carbon core and It has a containment space inside, and the carbon core is a porous carbon skeleton layer in the containment space, A carbon coating layer covering at least a portion of the outer surface of the porous carbon skeleton layer, A wave-absorbing material and silicon-based particles are independently distributed only in the region inside the carbon coating layer where the carbon core and the porous carbon skeleton layer exist, wherein the wave-absorbing material absorbs microwaves. Includes, The wave-absorbing material is a negative electrode active material containing one or more of the following: Fe₃O₄, WO₃, NiO, LaFeO₃, ZnO, and Co₃O₄.
2. The negative electrode active material according to claim 1, wherein, on a basis of the total mass of the wave-absorbing material, the content of the wave-absorbing material distributed in the porous carbon skeleton layer is 90 wt% or more, and the content of the wave-absorbing material distributed in the region where the carbon core exists is 10 wt% or less.
3. The content of the wave-absorbing material is 0.5 wt% to 15 wt% by mass of the porous carbon framework layer, and / or The negative electrode active material according to claim 1, wherein the content of the wave-absorbing material is 10 wt% or less by mass of the negative electrode active material.
4. The negative electrode active material according to claim 1, wherein the wave absorbing material satisfies at least one of the following conditions: the wave absorption range is 5.2 GHz to 15.9 GHz, the wave absorption bandwidth is 8.4 GHz to 10.7 GHz, and the particle size is 20 nm to 500 nm.
5. The negative electrode active material according to claim 1, wherein the silicon-based particles include one or more of silicon elemental, silicon oxygen material, and silicon carbon material.
6. The negative electrode active material according to claim 1, wherein the content of the silicon-based particles is 30 wt% to 70 wt% by mass of the negative electrode active material.
7. The negative electrode active material according to claim 1, wherein the porosity of the porous carbon skeleton layer is 40% to 70%, and / or the pore size of the porous carbon skeleton layer is 1 nm to 50 nm.
8. The particle size of the carbon core is 1 μm to 5 μm, The thickness of the carbon coating layer is 1 μm or less, The negative electrode active material has a Dv50 particle size of 10 μm or less, and a Dv90 particle size of 20 μm or less. The negative electrode active material according to claim 1, satisfying at least one of the following conditions.
9. The carbon core comprises one or more of graphite, porous carbon, and mesocarbon microbeads, and / or The negative electrode active material according to claim 1, wherein the carbon precursor material used to form the porous carbon skeleton layer and the carbon coating layer each independently comprises one or more of pitch, resin, soluble starch, sucrose, glucose, and polyacrylic acid ester.
10. The negative electrode active material according to claim 1, further comprising a carbon core coating layer that covers at least a portion of the outer surface of the carbon core, is located in the containment space, and has a wave-absorbing material distributed within it.
11. The negative electrode active material according to claim 10, wherein the mass ratio of the wave absorbing material to the carbon core coating layer is greater than the mass ratio to the porous carbon skeleton layer.
12. The negative electrode active material according to claim 10, wherein the thickness of the carbon core coating layer is 1 μm or less.
13. The negative electrode active material according to claim 1, wherein the resistivity at room temperature and under a pressure of 4 MPa is 100 mΩ·cm to 10000 mΩ·cm.
14. A step of mixing a carbon core material, a pore-forming agent, a carbon skeleton precursor material, and a solvent to obtain a first mixed solution, A step of mixing a wave-absorbing material with the first mixture to obtain a second mixture, The process of obtaining composite particles by spray molding and fluid drying treatment of the second mixture, The process involves applying a carbonization treatment and an activation treatment to the composite particles to obtain skeletal particles in which the carbon core is coated with a porous carbon skeleton layer, The process involves heating the aforementioned skeletal particles with microwaves and introducing a gas-phase silicon source to deposit silicon, thereby obtaining precursor particles. A step of obtaining a negative electrode active material by coating at least a portion of the outer surface of the aforementioned precursor particles with a carbon coating layer, A method for producing a negative electrode active material according to claim 1, including the method described in claim 1.
15. The method according to claim 14, further comprising the step of coating at least a portion of the outer surface of the carbon core material with a carbon core coating layer before preparing the first mixture.
16. The pore-forming agent contains one or more of the following: sodium chloride, potassium chloride, zinc chloride, sodium carbonate, potassium carbonate, zinc carbonate, zinc acetate, and ammonium acetate. The sum of the mass ratio of the pore-forming agent and the mass ratio of the carbon skeleton precursor material in the first mixture is 10 wt% to 70 wt%, The mass ratio of the pore-forming agent to the carbon skeleton precursor material is (10 to 1): (1 to 100), The method according to claim 14, which satisfies at least one of the following conditions.
17. A negative electrode sheet comprising the negative electrode active material described in claim 1.
18. A battery comprising the negative electrode active material described in claim 1.
19. An electrical device comprising a negative electrode active material according to any one of claims 1 to 13.
Citation Information
Patent Citations
Method for preparing Si / Fe / Fe3O4 / C composite material by using supercritical CO2 fluid medium
CN113793924A
Novel materials with highly durable lithium intercalation and methods for their manufacture
JP2022153561A
Anode active material, method for preparing same, and lithium secondary battery comprising same
WO2022270967A1